Role of magnetic resonance imaging in biometric evaluation of corpus callosum in hypoxic ischemic encephalopathy patients - Amit Garhwal; Ashwin S Patil (Journal of the Scientific Society, 2017)
Background: Corpus callosum (CC) has an important role in establishing hemispheric lateralization of function. Significance of this structure which is the primary white matter commissure of the brain lies in the fact that damage to the CC during development has been found to be associated with poor neurological outcome and neuropsychological performance. Magnetic resonance imaging (MRI) can precisely detect, localize, and evaluate damage to CC in hypoxic-ischemic encephalopathy (HIE) patients and assist in reaching to at an accurate anatomical diagnosis, thus heeling in further management of the patient. Objectives: The objective of this study is to analyze the effect of HIE on CC morphometry by assessing various diameters of CC. Materials and Methods: Fifty-four patients with history of hypoxic-ischemic injury referred to the Department of Radiodiagnosis were included in the study. All the patients were made to undergo MRI of the brain using Siemens Symphony Magnetom 1.5 Tesla scanner after taking informed consent for the same. The findings of MRI brain were assessed and analyzed. Data analysis was done using percentages of different diagnosis and outcomes made by MRI brain were computed and compiled. Results: In the present study, male predominance is seen, 77.78% patients were male and 22.22% were female. In the present study, maximum numbers of patients were <1 year of age (37.04%). In the present study, we see that the isthmus was the most commonly affected portion of CC. Children who did not cry at birth, born with low birth weight, low Apgar score were positively correlated with severity of damage to CC. Conclusion: From the present study, it was noted that MRI is very efficient tool in evaluating morphometry of CC in HIE. Its noninvasiveness and no exposure to ionizing radiation is an added advantage. However, experience and understanding of the principles are essential for accurate diagnosis.